PROS AND CONS OF PATENTING STEM CELLS - Damjanović, Gordana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
The evolution and transformation of research in the field of biotechnology are also reflected in patent rules. Gene patenting was first granted so that the further development of biotechnology, as well as the pressure from multinational biotechnology companies, would initiate prescription of patent protection of stem cells in certain legal systems. Research should provide a better understanding of the differentiation and development of stem cells, with potential consequences for healing from previously untreatable diseases, but they should also provide new ways of exploring fundamental issues in biology, such as the mechanism for growth of cells. Researchers, but mostly biotech companies, advocate therefore in favor of the provision of monopoly on the results of their research. A patent provides such a monopoly. Although remarkable progress has been made in the research of stem cells, many aspects of the use, especially of embryonic cells, have not been fully comprehensible and clear. Successful applications of products that use a stem cell derivative on the one hand and moral dilemmas that relate primarily to embryonic stem cells on the other have resulted in a debate that has affected many legal areas, such as the patent law. Such morally challenging products have caused great concern in the USA and the EU. However, these two entities have tried in different ways to solve the problem. Different views on law, ethics, and embryos have also affected different views regarding the patent protection of stem cells.